Implementation of the Assistance Programme for Child Victims of Sexual Violence at the Minahasa Regency Women’s Empowerment and Child Protection Office - Fitri H. Mamonto; Margareth Rantung; Charolina E. Runtu; Rahma Alhasni (Technium Social Sciences Journal, 2023)
The purpose of this study is to find out how the implementation of the mentoring program from the Office of Women’s Empowerment and Child Protection in Minahasa Regency in accompanying Child victims of Sexual Violence. The research method used is qualitative research and data collection techniques in this study are observation and interviews where the number of informants and informants is 8 people. Based on the results of research and findings in the field, it can be concluded that the Child Assistance Program for Victims of Sexual Violence at the Minahasa Regency Women’s Empowerment and Child Protection Office has not been fully implemented because the implementing policy is more focused on the mentoring process without touching the prevention process, so parents do not know what is happening. This must be done when there is sexual violence and there is still a lack of socialization from relevant agencies regarding sexual violence against children to the community